One-Pot Multicomponent Reactions in Deep Eutectic Solvents - Ayvaz, Aslıhan; Demirba, Sinem G.; Demirbaş, Ahmet; Demirba, Neslihan (Current Organic Chemistry, 2023)
The increasing environmental pollution and its detrimental impact on the ecosystem made scientists develop new chemical strategies involving eco-friendly chemicals, solvents, catalysts, atom-economical procedures, and alternative energy sources. Among these, deep eutectic solvents (DESs) are primarily low-melting mixtures of quaternary ammonium salt and hydrogen-bond acceptors. Low toxicity, easy preparation, low cost, biodegradability, low vapor pressure, and recyclability are the main advantages of DESs. Multicomponent reactions (MCRs) are efficient procedures for generating new libraries with high structural complexity. MCRs can give one product from at least three components in a single operation with high bond-forming efficiency, shortness, and structural diversity. Compared with conventional methodologies, the structural diversity, the convergent and atom economic character, the easy applicability of a one-pot operation, the accessibility to complex molecules, the minimized waste formation, and high selectivity are the main advantages of one-pot multicomponent reactions. The application of MCRs in eutectic solvents not only simplifies procedures but also displays more positive effects on the protection of the ecosystem.
Keywords: Biginelli reaction